Effectiveness of Ethanol Extract of Mangosteen Leaves (Garcinia mangostana L.) as Anti-diarrhea in Mice Induced by Oleum Ricini - Ahmad Khoirul Azwar; Shinta Mayasari; Mohammad Rofiq Usman (Indonesian Pharmacopeia Journal, 2025)
Diarrhea is a condition where a person experiences defecation with a soft or liquid consistency, with more frequent frequency (generally three or more times) a day One of the plants used as treatment for diarrhea is mangosteen leaves (Garcinia mangostana L). The leaves of the mangosteen plant (Garcinia mangostan L.) contain tannin compounds which can be useful as an antidiarrheal. Tannin is a substance that is effective as an adstringents, so it is thought to be able to provide an anti-dare effect. To determine the effectiveness of ethanol extract of mangosteen leaves (Garcinia mangostana L) as antidiarrhea in male white mice (Mus musculus) induced by oleum ricini. This research uses a type of laboratory experimental study using male mice (Muss musculus L) that have been induced with oIeum ricini. There were 15 mice used and divided into 5 groups, namely: negative control group (CMC Na 0.5%), positive control group (loperamide HCl) and treatment groups with dose concentrations of 250 mg/kgBW, 450 mg/kgBW and 650 mg/ kg BW. The research results showed that mangosteen leaves contain flavonoids and tannin compounds. This study shows the antidiarrheal activity value of 3 extract dose groups. There were 4 test parameters with the greatest antidiarrheal activity results at a dose of 650 mg/kgBB. The average result of the onset of diarrhea was 62.3 minutes, then the average result of the frequency of diarrhea was 5 times, while the duration of diarrhea was 85 minutes with an average feces weight of 0.99 grams. The ethanol extract of mangosteen leaves at a dose of 650 mg/kgBW had the most effective antidiarrheal activity in male (mus musculus) mice induced by oleum ricini. Key words: anti-diarrhoea, mangosteen leaves, loperamide; oleum ricini, garcinia mangostana